Measurement of Quantum of Damages for Wrongful Termination of Employment in Nigeria: Gleaning Lessons from Ghana and Malaysia - Abangwu, Nzeribe Ejimnkeonye; Oyibodoro, Ufuoma Garvin; Eyongndi, David Tarh-Akong; Shaba, Sampson; Opara, Faith Nwayemogho (Lentera Hukum, 2025)
In a master-servant employment relationship, when an employee’s employment is wrongfully terminated, the traditional measure of damages upon a successful legal challenge is the amount the employee would have earned during the agreed notice period. However, the National Industrial Court of Nigeria (NICN), empowered by the Constitution (Third Alteration) Act, 2010 to apply international best labour practices and International Labour Organisation (ILO) standards, has departed from this position. This departure was affirmed by the Court of Appeal (CA) in Sahara Energy Resources Ltd. v. Oyebola, where the court held that, in deserving cases, damages exceeding the ordinary notice period can be awarded. This paper utilises an analytical method to examine the impact of this decision on the jurisprudence of damages for wrongful termination in Nigeria. It probes whether the decision permits the NICN to award unpredictable damages that prejudice employers. The paper argues that the decision promotes employment security amidst Nigeria's unprecedentedly high unemployment rate. By examining current legislation and practice in Ghana and Malaysia, this research aims to draw lessons for Nigeria. It concludes that the decision is a welcome development. The paper recommends that the CA, as the final court on labour matters, should sustain this precedent, as it aligns the law with modern realities. Furthermore, the decision should be given statutory backing by amending relevant domestic labour legislation, as is the case in Malaysia and Ghana. Keywords: Dismissal, Ghana, Malaysia, Nigeria, National Industrial Court of Nigeria.